2013
DOI: 10.3389/fpsyg.2013.00626
|View full text |Cite
|
Sign up to set email alerts
|

Ode to positive constructive daydreaming

Abstract: Nearly 60 years ago, Jerome L. Singer launched a groundbreaking research program into daydreaming (Singer, 1955, 1975, 2009) that presaged and laid the foundation for virtually every major strand of mind wandering research active today (Antrobus, 1999; Klinger, 1999, 2009). Here we review Singer’s enormous contribution to the field, which includes insights, methodologies, and tools still in use today, and trace his enduring legacy as revealed in the recent proliferation of mind wandering studies. We then turn … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
148
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 183 publications
(160 citation statements)
references
References 113 publications
9
148
0
3
Order By: Relevance
“…However, given that adults spend 25-50% of their waking time mind wandering (Kane et al, 2007;Killingsworth & Gilbert, 2010;Song & Wang, 2012), it might sometimes be adaptive. Indeed, Singer's pioneering work claimed that "positive-constructive daydreaming" contributed to everyday problem solving, creativity, and imagination (Singer, 1966;McMillan, Kaufman, & Singer, 2013). Similarly, Klinger's investigations of "fantasy" emphasized the role of mind-wandering in goal striving (Klinger, 1971(Klinger, , 2013.…”
mentioning
confidence: 99%
“…However, given that adults spend 25-50% of their waking time mind wandering (Kane et al, 2007;Killingsworth & Gilbert, 2010;Song & Wang, 2012), it might sometimes be adaptive. Indeed, Singer's pioneering work claimed that "positive-constructive daydreaming" contributed to everyday problem solving, creativity, and imagination (Singer, 1966;McMillan, Kaufman, & Singer, 2013). Similarly, Klinger's investigations of "fantasy" emphasized the role of mind-wandering in goal striving (Klinger, 1971(Klinger, , 2013.…”
mentioning
confidence: 99%
“…While some like McMillan et al (2013) proposed mind-wandering as possibly a deliberate process of which one is aware, following Smallwood, McSpadden and Schooler (2007), here it is suggested that when one is 14 wandering, one is unaware of the process of wandering, nor does he or she choose to engage in it. Rather, only when one finds herself wandering, awareness is there to acknowledge having been wandering.…”
Section: Non-deliberate Processmentioning
confidence: 91%
“…Second, what we are suggesting is that our lacking a sense of agency over processes and/or content that comes to our minds spontaneously, does not rule out the possibility that there is perhaps a natural intelligence or evolutionary 'reasoning' behind these non-deliberate processes and content, of which we are unaware. Such indeed has been the position of some scholars in this field (Baars, 2010;McMillan et al, 2013;Raichle, 2015 an adaptive process that may be beneficial. This approach will enable us to present some theories that have been proposed in cognitive and neuroscience in educational terms, and later, to suggest some critical responses to these theories.…”
Section: Non-deliberate Processes As a Curricular Deliberationmentioning
confidence: 99%
See 2 more Smart Citations